INSURANCE OFFER AND THE REASON FOR THE UNDERDEVELOPED MARKET IN SERBIA - Pušara, Milorad (Journal of process management and new technologies, 2020)
This paper presents the current condition of the insurance market by creating an unpretentious review and pointing to the current deficiency of the insurance system in Serbia. It outlines some ideas that might solve certain issues and improve the current situation. Referred innovations that were introduced last year in the world market are very useful and can also serve as a good standard for joining the global insurance. Last but not least, the paper addresses the segment of insurance frauds as alarming incidences in need of attention. If we consider the "Basic Elements of Insurance", Risk, Premium, and Indemnity, and if we follow the development of the Insurance throughout the world, we recognize that technology development and reduced business costs imply greater Risks, a growing range of new products, decreased Premium, and stimulating increase of the Indemnity. This leads us to the conclusion that we must enter the race with the developed countries and accept the way of their business management by following the latest innovations in the insurance market in order to be competitive and competent.